2007
DOI: 10.1162/jocn.2007.19.5.866
|View full text |Cite
|
Sign up to set email alerts
|

ERP Evidence of Morphological Analysis from Orthography: A Masked Priming Study

Abstract: There is broad consensus that the visual word recognition system is sensitive to morphological structure (e.g., “hunter” = “hunt” + “er”). Moreover, it has been assumed that the analysis of morphologically complex words (e.g., “hunter”) occurs only if the meaning of the complex form can be derived from the meanings of its constituents (e.g., “hunt” and “er”). However, recent behavioral work using masked priming has suggested that morphological analysis can occur at an early, orthographic level, with little inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
130
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 41 publications
22
130
2
Order By: Relevance
“…This 'form-then-meaning' time-course is consistent with the temporal characterisation of the recognition of printed derived forms uncovered in previous research (e.g. Crepaldi et al, 2010;Lavric et al, 2007Lavric et al, , 2012Rastle et al, 2004). We believe that these data support the particular theory developed by Crepaldi et al (2010), which is based on the classical localist modelling tradition exemplified in work on speech production (e.g.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This 'form-then-meaning' time-course is consistent with the temporal characterisation of the recognition of printed derived forms uncovered in previous research (e.g. Crepaldi et al, 2010;Lavric et al, 2007Lavric et al, , 2012Rastle et al, 2004). We believe that these data support the particular theory developed by Crepaldi et al (2010), which is based on the classical localist modelling tradition exemplified in work on speech production (e.g.…”
supporting
confidence: 89%
“…Crepaldi et al, 2010;Lavric et al, 2007Lavric et al, , 2012Rastle et al, 2004). Further, this study adds to a remarkably consistent picture of the precise timing of the proposed morpho-orthographic segmentation process.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Taft and Forster, 1975). For example, Lavric et al (2007) reported comparable priming effects for pairs of words that were morphologically related (e.g. cleaner -clean) and pairs that only superficially had a morphological relation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other behavioral studies and the use of event-related potentials (ERPs) have questioned this theoretical view (e.g. Longtin et al, 2003;Rastle et al, 2004;Barber et al, 2002;Domínguez et al, 2004;Lavric et al, 2007).…”
Section: Introductionmentioning
confidence: 99%